Qualitative Exploration of Effective Policing Approaches to Raise Awareness of Gender- Based Violence Among Pupils in Chamwino District, Tanzania - Nemes, Joyce; Rwabishugi , Leticia (CV. Literasi Indonesia, 2025)
Teaching young children about Gender-Based Violence (GBV) requires effective, theory-based strategies to create conducive learning environments. This article examines the methods used by the Police Gender and Children's Desk (PGCD) to create awareness of GBV among pupils during school visits in Chamwino District, Dodoma, Tanzania, using Albert Bandura's social learning theory as a framework. In this qualitative analysis, four key themes emerge: interactive and participatory methods, question-and-answer sessions, multi-modal environmental messaging, and memory-enhancing strategies. Findings indicate that these methods facilitate observational learning, capture children's attention through songs (e.g., the “Don't Touch Me” song), enhance retention via repetition, and motivate children through rewards. Moreover, police officers serve as role models as they use their authority to foster message adoption and self-efficacy among pupils. Additionally, strategically placed slogans reinforce protective behaviors, illustrating Bandura's principle of reciprocal determinism. This article underscores the role of the PGCD in employing theory-based strategies for GBV education, and advocates for formalized training, standardized materials, collaboration with schools, and digital strategies to improve learning environments. Recommendations include formalization of social learning in PGCD training, creation of standardized educational materials, and provision of a theoretically grounded framework for enhancing education on GBV prevention across various contexts.